“many a lay and many a thing” - Nuttall, J (Cambridge University Press, 2018)
This chapter investigates Chaucer's usage of technical terminology to refer to verse-form and poetic technique. Chaucer uses the technical terms or jargon of poetry not just to name his own techniques or the techniques of others but also to pose questions to himself and to his readers. Chaucerian formal self-reference appears as purposeful muddling or inconclusive duplication of technical terms (by using two or more terms instead of one, by using technical terms idiosyncratically, or by creating dissonance between a poem's form and the label applied to it), creating a game of knowledge and expectation between Chaucer and his audience. Such self-reference exposes some of Chaucer's own attitude to poetic form, to technical virtuosity and to the capacity of English to imitate or surpass the forms of its classical and continental predecessors and rivals.